Teacher education around the world: What can we learn from international practice? - Darling-Hammond, Linda (European Journal of Teacher Education, 2017)
This article describes teacher education in jurisdictions around the world that have well-developed systems for teacher development. It examines teacher education policies and practices in Australia (with a focus on Victoria and New South Wales), Canada (with a focus on Alberta and Ontario), Finland and Singapore within the context of recruitment, preparation, induction, ongoing professional development and collective improvement of practice. It compares these practices with those in the United States, and evaluates challenges countries face in transforming their teacher development systems.